Knowledge, attitudes, and practices of vaccinators about expanded programs on immunization: a cross-sectional study - Azhar, Sunia; Rashid, Laiba; Islam, Taskeen; Akhtar, Samar; Hopkins, Kathryn L.; Sommers, Theresa; Ikram, Aamer; Anwer, Naveed; Maqbool, Nabeel Ahmed; Khan, Zakir; Ahmed, Naveed; Akhtar, Hashaam (Frontiers in Public Health, 2024)
Introduction The periodic evaluation of knowledge, attitudes, and practices (KAP) of healthcare workers, including vaccinators, concerning expanded programs on immunization (EPI) is very crucial for a better healthcare system. This study was carried out to assess the KAP of vaccinators about the EPI, including cold storage of vaccines and their practices related to vaccine cold chain management. Method A cross-sectional study was conducted from January 2022 to June 2022 among registered vaccinators in the twin cities (Islamabad and Rawalpindi) of Pakistan. A structured self-administered questionnaire (English and Urdu) was developed as per the Pakistan national EPI policy and strategic guidelines 2022 and World Health Organization (WHO) guidelines, as well as from earlier studies (Cronbach's alpha value of 0.734). The final questionnaire consisted of closed-ended questions in four sections, including sociodemographic information, knowledge (with dichotomous variables of yes/no), attitudes (with a 5-point Likert scale ranging from strongly agree to strongly disagree), and handling of vaccines and cold chain management. Completed questionnaires were entered into Microsoft Excel and then imported into SPSS version 25 for statistical analysis. Results A total of 186 vaccinators completely filled out their questionnaires, with a 97.9% response rate. More than half of the participants (57.5%) had no training related to EPI. Most of the respondents had a moderate to poor level of knowledge regarding EPI. The overall attitude was positive, and 57% of the participants strongly agreed that the national immunization programs can significantly contribute to the decrease in morbidity and mortality rates among children. In the current study, participants showed good practices toward EPI, vaccine storage, and cold chain management. The majority (93.5%) of the participants checked the expiry of vaccines at regular intervals to maintain the first expiry first out (FEFO) in their healthcare setting. Discussion In conclusion, most of the vaccinators had moderate to poor knowledge, a positive attitude, and good practices toward EPI, vaccine cold storage, and cold chain management. Lack of training among vaccinators on EPI was also observed. These findings have suggested that continuous training, education, and regular supervision of vaccinators in EPI are important for maximum immunization effectiveness and coverage.